STRATEGI PEMASARAN WEDDING PACKAGES PADA MY WEDDING ORGANIZER - Ni Nyoman Wulan Antari; Riza Wulandari (Badung: LPPM Universitas Triatma Mulya, 2020)
In developing a business in the field of marriage, My Wedding Organizer has designed several wedding packages for brides who want a party that is only attended by a few people (privacy). By working with several reception venues and several other wedding organizers, My wedding organizer has succeeded in making customers feel satisfied with the wedding packages offered. However, in 2019 My Wedding Organizer was not able to achieve the expected target, thus we conducted research aimed at increasing sales of wedding packages on My Wedding Organizer by making a strategy formulation by analyzing the marketing mix of 7P services consisting of products and services, prices, channels. / place of distribution, promotion, people, facilities (physical evidence) and processes based on a SWOT analysis. Based on the research of this study in increase of sales of wedding packages which decreased especially in 2019, namely the creation of a new strategy formulation is based on the SWOT analysis 7P. The conclusions of the study are based on the marketing mix by creating a SWOT matrix, from strategy SO, WO, ST and WT in strategy formulation it can be based on the 7P include product, price, distribution channels / place, promotion, people, processes, and the physical evidence. It is recommended to use the hotel management corporate strategy formulation and business unit strategy formulation, with the wedding venue evaluate and innovate to create a new wedding packages to explore creativity in the promotional aspect of wedding.